We are the ship : the story of Negro League baseball - Nelson, Kadir (New York : Jump at the Sun/Hyperion Books for Children, 2008)
Using an "Everyman" player as his narrator, Kadir Nelson tells the story of Negro League baseball from its beginnings in the 1920s through the decline after Jackie Robinson crossed over to the majors in 1947. Illustrations from oil paintings by artist Kadir Nelson.
Includes bibliographical references and index.
Keywords: Negro leagues -- History -- Juvenile literature; African American baseball players -- Juvenile literature; Baseball -- United States -- History -- Juvenile literature